GEOLOGY AND GEOTHERMAL SYSTEM BOUNDARIES DETERMINATION OF SLAMET MOUNTAIN, BANYUMAS?PURBALINGGA DISTRICT, CENTRAL JAVA - Hijriyahtia, Faatihah
The research area is located on the slopes of Southeast Slamet Mountain, covering Banyumas and Purbalingga Regencies. Based on the UTM coordinate system, the study area is at 9193000?9186700 mN and 302000?321400 mE in zone 49 S (WGS 1998). The study area is approximately 120 km2. One method of determining the boundaries of hydrothermal volcanic geothermal systems is to use a lateral flow analysis (outflow) based on the chemical composition of the water. Analysis of contaminated cold springs around geothermal manifestations is expected to help determining the boundaries of geothermal systems. The method of grouping contaminated cold springs is based on geological studies and water chemistry studies. Water chemistry studies consist of anomalous analysis of temperature, pH, and TDS, analysis of water types and water facies, Schoeller diagram, and stable isotope analysis. Geologically, the study area consists of 10 stratigraphic units. The units from old to young are Pyroclastic Fall Tuff Unit (Ktp), Pyroclastic Flow Breccia-Tuff Unit (Ktb), Pyroclastic Flow Breccia Unit (Msb), Andesite Lava Hill Unit (Mgl), Andesite Lava Unit of Khuluk Malang (Mla), Andesite Lava Unit 4 of Young Slamet (Stl4), Andesite Lava Unit 3 of Young Slamet (Stl3), Andesite Lava Unit 2 of Young Slamet (Stl2), Andesite Lava Unit 1 of Young Slamet (Stl1), and Aluvial Unit (Al). Cold springs in the study area are geologically divided into Khuluk Malang’s springs, which is Curug Jenggala (CJG), and Khuluk Slamet Muda’s springs, such as Pancuran 3 Cold Spring (DP3), Pancuran 7 Cold Spring (DP7) , and Curug Grenjang (CJG). Anomaly content of the amount of dissolved solids in cold springs occurs in Pancuran 3 Cold Spring (DP3), which has a TDS content of more than 100 ppm. The acidity of springs in the study area generally has a pH range close to neutral conditions (pH = 7). The results of the water type analysis showed that in general cold springs are included in the bicarbonate water type, while hot springs are included in the chloride-bicarbonate-sulfate water type. These results indicate that cold springs in the study area are included in the outflow zone. Anomalies occur in Pancuran 3 Cold Spring (DP3), which is included in the chloride-bicarbonate water type. The high content of Cl in these springs indicates the alleged thermal water contamination. The pattern of ion concentration charts in the Schoeller Diagram shows the similarity of the trend of Pancuran 3 Cold Spring (DP3)’s graph to the Pancuran 3 Hot Spring (PP3)’s and Pancuran 7 Hot Spring (PP7)’s graph. Integration of the results of geological studies and water chemistry studies shows the suspected cold springs to be contaminated with thermal fluids in the geothermal system of the Mount Slamet. These cold spring is Pancuran 3 Cold Spring (DP3) and Pancuran 7 Cold Spring (DP7). Meanwhile, the boundary of the geothermal system of the Southeast Slamet Mountain is thought to be influenced by the existence of the Baturraden Horizontal Fault in the southwest?northeastern direction that formed at tersier epoch.